Getting under the skin: Physiological stress and witnessing paternal arrest in young children with incarcerated fathers. Issue 5 (25th February 2021) - Muentner, Luke; Kapoor, Amita; Weymouth, Lindsay; Poehlmann‐Tynan, Julie
Abstract: U.S. jails see nearly 11 million annual admissions, rates that disproportionately affect men of color—more than half of whom are fathers. An estimated 7% of U.S. children experience the incarceration of a parent, increasing their risk for poor developmental and health outcomes. Although stress processes are often suggested as an underlying mechanism linking paternal incarceration to child well‐being, few studies have examined such links. To study how witnessing a father's arrest prior to incarceration in jail relates to children's stress processes, we collected data on 123 individuals from 41 families with young children whose father was in jail, including collecting hair from 41 children, and analyzed their cumulative stress hormones, cortisol, and cortisone. Results indicate that children had higher cumulative stress hormone concentrations when they witnessed their father's arrest. Moreover, there was evidence of a blunted stress reaction in children who witnessed the arrest and who also had high levels of ongoing behavioral stress symptoms, similar to findings in Post‐Traumatic Stress Disorder studies. Long‐term exposure to stress can have deleterious effects on children's brain development, further increasing risk for developmental psychopathology. Findings have implications for criminal justice approaches that safeguard children during parental arrest.